Exploring transformative pedagogy in the context of a human rights and visual arts course - Gollifer, Susan; Jónsdóttir, Ásthildur (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
In this paper we present some lessons learned from our experience of designing, implementing and assessing a student-centred course as part of the ActSHEN project. The human rights and visual arts course was run as a summer course for Edda Norden collaboration including the Nordic and Baltic teacher art education universities. The course started with an online discussion, readings and reflections in June, followed by a five-day workshop in August 2015 at the Iceland Academy of Arts (IAA). The course was framed by sustainability goals responsive to wicked problems understood as those “characterized by high levels of complexity, ambiguity, controversy and uncertainty both with respect to what is going on and with respect to what needs to be done” (Lotz-Sisitka, Wals, & Kronlid, 2015). We wanted to understand how transformative pedagogy within the arts is able to support struggles for justice and human rights. Drawing on data collected from the course evaluation process, we recognised emerging ethical dilemmas that students and educators face when engaging with pedagogies that aim to respond to wicked problems.